Importancia de la Administración Financiera y su impacto en el desarrollo de las Actividades del Departamento de Talento Humano del Banco de Pichincha, en la ciudad de Babahoyo – provincia de Los Ríos - Vera Ramos, Bryan Agustin (2022)
The importance of effective financial management for companies today depends largely on financial planning, which must be carried out on the basis of financial and managerial knowledge that enables the achievement of the objectives and goals of the organization or business. The origin or birth of financial management is found mainly in the so-called Industrial Revolution. The growth of countries depends on how their business develops, and organizations depend on their workers, so implementing the right policies and strategies for human resource management becomes important for employers. The talent department works with people who are a fundamental part of the company. But talent, selection, training or performance evaluation are not the only things we come across every day. Human resource management is one of the most important areas of organizational administration, since people are the most important asset of any company. The functions of the Department of Human Talent and Financial Administration cannot operate their development in isolation; both fields are dependent on each other. If organizations focus only on economic capital, budget and financial balance without taking into account human capital, the organization will have a great impact on the risk of critical processes such as hiring and retaining the best talent in the company. The way around this is to involve HR managers in creating the organization's strategy and goals.